APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK INVENTARISASI DAN EVALUASI ASET BANGUNAN MILIK PEMERINTAH KOTA SURABAYA (STUDI KASUS : SURABAYA PUSAT) - Taufik, Muhammad; Anugraha, Adindha Surya (GEOID, 2016)
Surabaya is the capital city of East Java Province and the second largest population in Indonesia after DKI Jakarta in which has 2.947.816 populations.The Increase of the building assets belonging to the Surabaya Government is not consistent with the good asset management by the government. Thus, this condition causes some of the government assets are change over towards the private parties due to such legal problems, for example the absence of building certificate. Therefore, inventoryand evaluating towards the building assets of Surabaya Government are necessary to be conducted.This research took place in Central Surabaya including Genteng District, Tegalsari District, Bubutan District and Simokerto District. Hence, this research aims to mapping the assets of Surabaya Government to establish the Geographic Information System (GIS), and also to evaluate the legal aspects of Surabaya Government buildings assets. This research use data from the Departemen of Building and Land Management, Departement of Education dan Departemen of Healthand also any other data obtained during the research.By using GIS, the evaluation of the legal aspects found that the buildings assets owned by Surabaya Government in Central Surabaya in which do not have a certificate is about 70,22% and only 29,78% of building assets in which already have the certifiacte